Is “Self-Experience” Really a Transdiagnostic Concept? Preliminary Evidence in Favor of the Transdiagnostic Conception of Functional Analytic Psychotherapy - González Palma, Ana María; Sánchez-Sánchez, Laura C.; Garcia-Montes, José Manuel (Frontiers in Psychiatry, 2021)
Functional Analytic Psychotherapy (FAP) offers a radically behavioral and transdiagnostic conception of the formation of the “self” and the appearance of a diversity of psychological problems. In spite of its interest, and the progress it led to at the time, as far as we know, the FAP approach to understanding the development of mental disorders has not been empirically tested. This study examined the extent to which a wide variety of psychological disorders (somatization, obsessive-compulsive, interpersonal sensitivity, depression, anxiety, hostility / aggressiveness, phobic anxiety, paranoid ideation and psychoticism) and a global index of psychopathological severity may in fact be linked to problems of the “self” according to the FAP conception. Two questionnaires, one related to self-experience according to FAP and the other to find the scores on several different psychopathology scales, were administered to 280 adult Spaniards for this purpose. The results confirmed the transdiagnostic nature of “self”-experience. There are significant and strong correlations between all the psychopathology scales studied and self-experience. Linear regression analyses also show that, along with age and gender, in some cases, the score on self-experience predicts each and every one of the psychopathological variables studied, in addition to the global severity index. These results are discussed in regards to the possibility of studying the development of the self according to practices in the construction of the private experience and its influence in the development of psychological disorders. In addition, limitations and suggestions for future research that builds on the findings of this study are provided.